Cataract Surgery and Visual Acuity in Elderly Japanese: Results of Fujiwara-kyo Eye Study - Miyata, Kimie (Biores Open Access, 2017)
The aim of this study was to determine the presence of prior cataract surgery and best-corrected visual acuity (BCVA) in an elderly Japanese cohort. The Fujiwara-kyo Eye Study was a prospective, population-based, cross-sectional epidemiological study. The subjects were ≥68 years who lived in the Nara Prefecture and responded to recruitment notices. All of the subjects underwent comprehensive ophthalmological examinations, and the sociodemographic information and medical history, including prior cataract surgery, were obtained by answers to a questionnaire. The associations between the BCVA, age, sex, and history of cataract surgery were determined. A total of 2,873 subjects whose mean age was 76.3 ± 4.9 (mean ± standard deviation) years were studied. The mean BCVA was −0.020 ± 0.14 logarithm of the minimum angle of resolution units, and it was significantly better in the group with education ≥13 years (p < 0.01). Overall, 24.2% of the subjects had undergone cataract surgery, and 41.7% of the subjects ≥80 years had undergone cataract surgery. The incidence of prior cataract surgery increased with increasing age (p < 0.001 for trend). The mean BCVA of eyes with cataract surgery was significantly better than that of eyes without cataract surgery in subjects ≥80 years (p < 0.01). Visual acuity was generally good in this cohort of elderly Japanese subjects. In this cohort, 24.2% of the subjects had undergone cataract surgery, and the subjects ≥80 years had better BCVA than those without cataract surgery.